The role of water alternatives in bread formulation and its quality; An emerging source of sustainable and cost-effective bakery improvers - Alireza Sadeghi; Zahra Kardooni; Maryam Ebrahimi; Elham Assadpour; Seid Mahdi Jafari (Future Foods)
Bread as staple food worldwide has a fundamental role in our daily diet. Accordingly, its fortification with sustainable, cost-effective and clean-label bakery additives has received considerable attention. Recently, increasing efforts has been devoted to apply potential water alternatives (WAL) in bread formulation for its enrichment. Water is one of the most important ingredients in bread formulation, which has undeniable effects on rheological behaviors of the manufactured dough, subsequent textural features and other quality characteristics of the final product. There are also some promising reports about potential WAL in bread-making process. These WAL can be categorized in three main groups including dairy-based, plant-based and fermented extracts that are reviewed in the present article. These ingredients have crucial effects on the quality indices of the produced bread. Production of fortified functional bread with improved sensory attributes, enhanced nutritional values, extended shelf-life and modified texture are some of the emerging potentials of these WAL in bakery industries. Protein content, nutritional profile, bioactive ingredients and antioxidant activity of these WAL are also key parameters involved in their techno-functional capabilities of the produced bread.